Surprise: user-controlled granular privacy and security for personal data in SmarterContext (2012)
The Smart Internet relies on the exploitation of information obtained from interactions of users with web applications. A critical aspect for its success is the adoption of mechanisms that guarantee the protection of information sensitive to users. This paper presents Surprise, our solution to empower users with privacy and data security control for the access to their information, stored in Personal Context Sphere repositories. These repositories are defined and maintained by SmarterContext, our Smart Internet infrastructure that improves the quality of user experience in their interactions with web applications.